SDGs-Based Economic Performance Measurement in the Green Tourism Sector - Yudhi Anggoro; Sarlotha Selan; Mahyadi Mahyadi (PT. Anagata Sembagi Education, 2025)
The growth of the tourism sector as an economic driver has increasingly been accompanied by environmental and social pressures, highlighting the need for sustainable green tourism approaches. However, sustainability claims in tourism are often not supported by structured economic performance evaluation frameworks aligned with sustainable development objectives. This study aims to analyze the economic performance of the green tourism sector using the Sustainable Development Goals (SDGs) as an evaluative framework. The study adopts a qualitative descriptive–analytical approach by examining the alignment between SDG-based economic indicators, green tourism policies, and implementation practices. The analysis is conducted through mapping relevant SDG economic indicators, reviewing tourism policy documents and official reports, and identifying gaps between economic performance outcomes and sustainability principles. The findings indicate that the SDGs framework enables a more comprehensive evaluation of green tourism economic performance than conventional approaches, particularly in assessing the quality and sustainability of economic impacts. The study also reveals misalignments between economic growth orientation and the achievement of sustainability goals in green tourism practices. This study concludes that SDGs provide a critical analytical framework for evaluating and guiding green tourism development toward sustainable economic outcomes.